International Agreements, Judah in Egypt, and the Problem of "Language": A Verbal Pattern to Explain שְׂפַת כְּנַעַן in Isa 19:18 - Boyd, Samuel (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2024)
The phrasing in Isa 19:18 מדברוֹת שׂפת כנען has proved vexing linguistically and historically. In this article, I explore previous proposals and offer support for a non-linguistic reference to the idiom based on verbal parallels elsewhere as well as cognate evidence. I conclude with further reflection on the idiom in Isa 19:18 and broader implications from this study, which includes observations about the semantics of שׂפה based on parallel uses of the lexeme in the Hebrew Bible.